Development of Integrated Thematic Learning Modules of Islamic Values for Grade VI Students at Elementary Madrasahs - Dewi, Ramla; Thaha, Hisban; Hutami, Eka Poppi; Maeduereh, Mustafakama (Journal of Indonesian Islamic Studies, 2024)
This study aims to develop a thematic learning module integrated with Islamic values on the sub-theme "Working Together to Achieve Goals" for grade VI students at MI Al-Ikhlas Balebo. The study used the Research and Development (R&D) method with a 4D development model consisting of the Define, Design, Develop, and Disseminate stages. At the Define stage, a needs analysis was conducted through interviews and questionnaires to identify the challenges faced by students and teachers in learning. Based on the results of the analysis, the module was designed with attractive illustrations and clearer materials to improve student understanding. The Develop stage involved validation tests by experts in the fields of language, materials, and religion, with an average validity result of above 90%, indicating that the module is suitable for use in learning. In addition, the practicality test showed that this module is very practical with an average value of 88.12%. This module not only helps students understand the material better, but also instills Islamic values in the learning process. This study concludes that the developed learning module is effective and relevant in improving the quality of learning and the formation of students' religious character.